Describing reporting guidelines for health research: a systematic review. - Moher, D; Weeks, L; Ocampo, M; Seely, D; Sampson, M; Altman, D; Schulz, K; Miller, D; Simera, I; Grimshaw, J; Hoey, J (2011)
OBJECTIVE: To describe the process of development, content, and methods of implementation of reporting guidelines for health research. STUDY DESIGN AND SETTING: A systematic review of publications describing health research reporting guidelines developed using consensus. RESULTS: Eighty-one reporting guidelines for health research were included in the review. The largest number of guidelines do not focus on a specific study type (n=35; 43%), whereas those that do primarily refer to reporting of randomized controlled trials (n=16; 35%). Most of the guidelines (n=76; 94%) include a checklist of recommended reporting items, with a median of 21 checklist items (range: 5-64 items). Forty-seven (58%) reporting guidelines were classified as new guidance. Explanation documents were developed for 11 (14%) reporting guidelines. Reporting-guideline developers provided little information about the guideline development process. Developers of 50 (62%) reporting guidelines encouraged endorsement, most commonly by including guidelines in journal instructions to authors (n=18; 36%). CONCLUSIONS: Reporting-guideline developers need to endeavor to maximize the quality of their product. Recently developed guidance is likely to facilitate more robust guideline development. Journal editors can be more confident in endorsing reporting guidelines that have followed these approaches.